Investigation on the Movement and Fracture Characteristics of an Extra-Thick Hard Roof during Longwall Panel Extraction in the Yima Mining Area, China - Hongwei Wang; Daixin Deng; Ruiming Shi; Guozhen Yang; Shuo Xu; Yaodong Jiang (Geofluids)
As an extra-thick hard roof is a significant contributing factor to frequently induced sudden roof collapse accidents and coal bursts, this study investigates the relationship between extra-thick hard roof movement and mining-induced stress using physical experiments and numerical simulation methods based on mining activities in a longwall panel in the Yima mining area, Henan province, China. The results suggested that the movement and failure processes of the extra-thick roof could be divided into three main periods: the undisturbed, movement stabilization, and sudden collapse periods. The roof displacement remained essentially unchanged during the undisturbed period. During the movement stabilization period, the displacement gradually increased into the upper roof. However, the extra-thick main roof remained undisturbed until the immediate roof experienced its fourth periodic caving in the physical model. Consequently, the displacement expanded rapidly into the extra-thick main roof during the sudden collapse period and the strain energy was violently released when it accumulated in the extra-thick main roof. Additionally, the mining-induced stress was characterized by a sudden decrease in the gradual increase trend when the extra-thick roof instantly collapsed. The deformation and fracture of the extra-thick roof could cause a sudden decrease in the mining-induced stress and lead to continuous and unstable subsidence pressure exerted on the mining panel and roadway. This significantly contributes to the occurrence of coal bursts.